Emotion and attention interaction: a trade-off between stimuli relevance, motivation and individual differences - Oliveira, Leticia; Mocaiber, Izabela; David, Isabel A.; Erthal, Fatima; Volchan, Eliane; Pereira, Mirtes (Frontiers in Human Neuroscience, 2013)
Mounting evidence suggests that the neural processing of emotional stimuli is prioritized. However, whether the processing of emotional stimuli is dependent on attention remains debatable. Several studies have investigated this issue by testing the capacity of emotional distracters to divert processing resources from an attentional main task. The attentional load theory postulates that the perceptual load of the main task determines the selective processing of the distracter. Although we agree with this theory, we also suggest that other factors could be important in determining the association between the load of the main task and distracter processing, namely, (1) the relevance of the to-be ignored stimuli and (2) the engagement in the main task resulting from motivation. We postulate that these factors function as opposite forces to influence distracter processing. In addition, we propose that this trade-off is modulated by individual differences. In summary, we suggest that the relationship between emotion and attention is flexible rather than rigid and depends on several factors. Considering this perspective may help us to understand the divergence in the results described by several studies in this field.